Kajian Reflektif Teori Thorndike Dalam Konteks Representasi Matematis Berdasarkan Ideologi Utilitarian - Rila Septia Pratama Putri Rila; Tian Abdul Aziz (Pendidikan Matematika FKIP Universitas Mataram, 2022)
Mathematical representation is the center of mathematics learning activities. Representations help students understand various forms of mathematical presentation. Strengthening mathematical representation in learning is based on learning theory, namely Thorndike Theory. American Educational Psychologist Edward L. Thorndike has a